A taxonomic revision of the soil-feeding termite genus Anhangatermes (Isoptera: Termitidae: Nasutitermitinae) - Oliveira, Danilo E.; Cunha, Hélida F.; Constantino, Reginaldo (Zootaxa, 2014)
The taxonomy of Anhangatermes Constantino 1990 is revised. Four new species are described: Anhangatermes anhanguera, sp. n., Anhangatermes eurycephalus, sp. n., Anhangatermes juruena, sp. n., and Anhangatermes pilosus, sp. n. The imago of Anhangatermes is described for the first time (A. pilosus). A key to the species of the genus based on soldiers and workers is provided. The diagnosis of the genus is updated to accommodate the new species. The geographic range of the genus is expanded to the Cerrado region of Central Brazil. The gizzard armature of the worker of Anhangatermes is described in detail for the first time.